First-principle study on the structural and electronic properties of H2S and SO2 adsorption on Pd-doped MoS2 monolayer. (1st February 2020) - Gui, Yingang; Cao, Wenhai; Sun, Zhilin; Lv, Gang; Tang, Chao
Abstract : The partial discharge in SF6 -insulated equipment produces characteristic decomposition products: SO2 and H2 S. The characteristic decomposition products vastly speed up the process of discharge faults. Based on density functional theory (DFT) calculation, single layer Pd-doped MoS2 (Pd-MoS2 ) is adopted as the adsorbent to adsorb SO2 and H2 S to ensure the operational stability of SF6 -insulated equipment. The adsorption energy, charge transfer and structure parameters of SF6, H2 S, and SO2 adsorption on the Pd-MoS2 monolayer are analysed to find the most stable adsorption structure. The molecular orbital theory, total density of states and partial density of states are studied to analyse the adsorption mechanism. The results show that Pd-MoS2 adsorbent possesses high catalytic activity and excellent adsorption performance to H2 S and SO2 by strong chemical adsorption. This study is of great significance to ensure the operational stability of SF6-insulated equipment by removing these characteristic decomposition products. GRAPHICAL ABSTRACT: